Stress - edited by George Fink (Academic Press, an imprint of Elsevier, 2016)
Stress: Concepts, Cognition, Emotion, and Behavior: Handbook in Stress Series, Volume 1, examines stress and its management in the workplace and is targeted at scientific and clinical researchers in biomedicine, psychology, and some aspects of the social sciences. The audience is appropriate faculty and graduate and undergraduate students interested in stress and its consequences. The format allows access to specific self-contained stress subsections without the need to purchase the whole nine volume Stress handbook series. This makes the publication much more affordable than the previously published four volume Encyclopedia of Stress (Elsevier 2007) in which stress subsections were arranged alphabetically and therefore required purchase of the whole work